Penggunaan Media Audio Visual dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran SKI di Kelas VII MTs Darussa'adah Petanahan - Saputri, Rani; Hidayah, Khoirul Laili; Fatimah, Siti (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This study aims to process the use of Audio Visual Media in Increasing Student Learning Motivation in SKI Subjects in class VII MTs Darussa`adah Petanahan and to find out the increase in student motivation after applying Audio Visual media to SKI learning in Class VII MTs Darussa`adah Petanahan. This research is a classroom action research conducted in two cycles, with two meetings in each cycle. The subjects of this study were SKI subject teachers and class VII students. The data in this study were taken using data collection techniques in the form of tests and non-tests. The results showed that there were changes in the pre-action results, cycle I, and cycle II. In the pre-action, only about 27% had motivation to learn. In cycle I, the percentage increased to 49%. Then, after reflection on cycle II, student motivation reached 86%.